“Implementation of Blue Ocean Strategy (BOS): study on the role of Chief Minister Office, Division of Human Resource as a Change Agent” / Nor Syafiqah Abdullah and Rojita Anam - Abdullah, Nor Syafiqah; Anam, Rojita (Faculty of Business and Management, 2013)
Blue Ocean Strategy (BOS) is the one of the management concept that is needed to be applied in any organizations. Division of Human Resource (BPSM) should take the opportunity to adapt Blue Ocean Strategy (BOS) in the organization as a respond and support to our Prime Minister’s announcement to encourage government servants to implement the Blue Ocean Strategy (BOS). The purpose of the implementation of Blue Ocean Strategy (BOS) is to ensure that government servants will show creative thinking and be more innovative. Beside that, through the implementation of Blue Ocean Strategy (BOS) it can help the government to make the necessary transformation in delivery of the public service. Therefore, these studies conducted focused on the “Implementation of Blue Ocean Strategy (BOS): Study on the role of Chief Minister Office, Division of Human Resource as a change agent”. The main objective of this study is to determine whether the Blue Ocean Strategy(BOS) is successfully implemented by the human resource division as an agent of change in their department.Thus, the human resource division (BPSM) used the theory in Blue Ocean Strategy(BOS) to measure their role as an agent of change. As a result, the Human Resource Division (BPSM) was successful in implementing the Blue Ocean Strategy(BOS) in the organization and played the role as an agent of change.